Modelling and optimisation of planar matrix transformer for high frequency regulated LLC converter. Issue 3 (14th January 2020) - Wu, Liang; Xiao, Long; Zhao, Jun; Chen, Guozhu
Abstract : For high‐frequency high‐current low‐voltage applications, planar matrix transformer for unregulated LLC converter has been adopted to achieve high power density and high efficiency. Compared to unregulated LLC converter, the phase shift between the primary current and the secondary current of the matrix transformer is larger in regulated LLC converter as a result of lower magnetising inductance. Thus, the conventional winding loss model is not applicable to the matrix transformer for regulated LLC converter. Aiming at this problem, an accurately winding dc resistance model and an analytic winding ac resistance model are proposed in this study to calculate the winding loss of the matrix transformer. In addition, lower magnetising inductance also causes more serious fringing field near the air gap. Then, a calculation method to model the winding loss due to the fringing field is investigated. With the proposed model, design and optimisation of the matrix transformer for regulated LLC converter are described in detail subsequently. The proposed model is verified by a Gallium Nitride based 400 W LLC converter prototype with a power density of 443 W/in 3 and a peak efficiency of 96.1%.